The performance of reliability and validity using 5 and 7 likert point scales / Fatin Qistina Awang ,Nur Izzati Syaziah Ab. Gani and Nurul Adawiyah Mohd Zulkifli - Awang, Fatin Qistina; Ab. Gani, Nur Izzati Syaziah; Mohd Zulkifli, Nurul Adawiyah (2019)
Determination of number Likert point scale is one of the issues that should be compromised by the researchers to construct the questionnaire in social study. The objective of the present study is to review literatures regarding the influence of different Likert point scale on reliability of measurement reflective model. The study also gives a review on validity of the measurement reflective model when using different Likert point scale. The result indicates that 7 Likert point scale shows the highest reliability and validity are better compared to 5 Likert point scale